1992
DOI: 10.1111/j.1527-3466.1992.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin: The Promising Antithrombotic

Abstract: It has long been known that medicinal leeches (Hirudo medicinalis) contain a substance with anticoagulant properties. In early studies, aqueous extracts and dry preparations from leeches containing minute amounts of the active substance were used to prevent blood from clotting. Only after the development of protein chemistry and the elucidation of the biochemistry of blood coagulation was the anticoagulant agent, hirudin, isolated and its chemical nature and mode of action clarified.The historical background o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 101 publications
1
31
0
Order By: Relevance
“…With regard to aPTT prolonga tion, rhirudin shows two-phase kinetics, with a ti/j a, p of, on average, 0.5 and 67.9 min respectively. These findings are in good agree ment with recently published results [2,24], The hirudin analogue, however, shows onephase kinetics, with a ty2 of 5 min.…”
Section: Pharmacokineticssupporting
confidence: 82%
See 2 more Smart Citations
“…With regard to aPTT prolonga tion, rhirudin shows two-phase kinetics, with a ti/j a, p of, on average, 0.5 and 67.9 min respectively. These findings are in good agree ment with recently published results [2,24], The hirudin analogue, however, shows onephase kinetics, with a ty2 of 5 min.…”
Section: Pharmacokineticssupporting
confidence: 82%
“…Surprising ly, an analogous bivalent inhibitor, which consists of a peptide corresponding to the carboxy terminal region (amino acids 53-64) of hirudin linked to a Z)-Phe-Pro-Arg-Pro pep tide via a (Gly)4-residue at the amino-termi nal end, demonstrated significant anticoagu latory ability, despite the fact that the individ ual components mediate only relatively weak inhibitory effects. Other authors have already reported in detail on the biochemical and bio logical properties of both substances [2,7,11], In a series of in vitro and in vivo test systems the superiority of both inhibitors over heparins was demonstrated [ 13,[27][28][29]. However, there are only few comparative studies of rhi rudin and this analogue [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special mixing device was used which allowed supplementation of the native blood with an antithrombotic compound under continuous flow conditions. This report describes the effects ofrecombinant (rec.) hirudin (34), heparin, and the selective, reversible thrombin in- hibitor Ro Fig. 1 is FCS, 50 ,g/ml endothelial cell growth factor, and 100 gg/ml heparin.…”
Section: Introductionmentioning
confidence: 99%
“…Lepirudin inactivates thrombin by forming a tight 1:1 complex involving noncovalent interactions without the need of a cofactor. Its half-life is 1.5 hr and is excreted through the kidneys [14]. Both argatroban and lepirudin can be monitored by an activated partial thromboplastin time (aPTT).…”
Section: Discussionmentioning
confidence: 99%